Prospective Study of the Surgical Techniques Used in Primary Rhinoplasty on the Caucasian Nose and Comparison of the Preoperative and Postoperative Anthropometric Nose Measurements - Berger, Cezar Augusto Sarraf (Int Arch Otorhinolaryngol, 2014)
Introduction The knowledge and study of surgical techniques and anthropometric measurements of the nose make possible a qualitative and quantitative analysis of surgical results. Objective Study the main technique used in rhinoplasty on Caucasian noses and compare preoperative and postoperative anthropometric measurements of the nose. Methods A prospective study with 170 patients was performed at a private hospital. Data were collected using the Electronic System Integrated of Protocols software (Sistema Integrado de Protocolos Eletrônicos, SINPE©). The surgical techniques used in the nasal dorsum and tip were evaluated. Preoperative and 12-month follow-up photos as well as the measurements compared with the ideal aesthetic standard of a Caucasian nose were analyzed objectively. Student t test and standard deviation test were applied. Results There was a predominance of endonasal access (94.4%). The most common dorsum technique was hump removal (33.33%), and the predominance of sutures (24.76%) was observed on the nasal tip, with the lateral intercrural the most frequent (32.39%). Comparison between preoperative and postoperative photos found statistically significant alterations on the anthropometric measurements of the noses. Conclusion The main surgical techniques on Caucasian noses were evaluated, and a great variety was found. The evaluation of anthropometric measurements of the nose proved the efficiency of the performed procedures.